Decision support systems IV : information and knowledge management in decision processes : Euro Working Group Conferences, EWG-DSS 2014, Toulouse, France, June 10-13, 2014, and Barcelona, Spain, July 13-18, 2014, Revised selected and extended papers /: information and knowledge management in decision processes : Euro Working Group Conferences, EWG-DSS 2014, Toulouse, France, June 10-13, 2014, and Barcelona, Spain, July 13-18, 2014, Revised selected and extended papers. (2015) - Unknown
No abstract available